The reflective pedagogical portfolio in the promotion of critical learning in education students - Carbajal Lavado, Napoleón Santiago (2021)
The research problem was what are the pedagogical conceptions, rationality, emotionality, practices, tools and instruments that underlie and are handled in the teaching and evaluation process of the pedagogical portfolio? And what pedagogical conceptions should we assume and  what practices and instruments should we develop in the teaching and evaluation of the pedagogical portfolio to promote the critical learning of the students who participate in the courses that I develop? We worked with a qualitative approach and the leading critical action research modalityin the classroom. The participants were 30 students from the academic programs of Initial Education, Primary, Communication and Computing of the Institute of Higher Education Pedagogical Public “Indoamérica” of Trujillo, Perou. The process followed was: diagnosis on the use of the portfolio, proposal and application of a reflective portfolio improvement plan. The quantitative results were processed through the SPSS 22 program, specifically the “t” with 29 degrees of freedom and the qualitative ones through the systematization-reflection workshops. The results show that the reflective pedagogical portfolio promotes the learning of critical thinking progressively. Likewise, the achievements and difficulties of using the portfolio as a learning-teachingtool are highlighted.